Formulation of Mixed-Matrix Membrane (PSF/Zeolite) for CO2/N2 Separation: Screening of Polymer Concentration - Chen, Chee Lek; Sunarti, Abd Rahman (Scientific Research, 2015)
This research investigates the permeability of CO2 and N2 as well as selectivity of CO2 over N2 of polysulfone (PSF) mixed matrix membranes filled with zeolite 4Å particles. The membranes were prepared by solution-casting method and utilized to determine the permeation rates of N2 and CO2. It was characterized by FTIR and the gas separation performance was analysed by Design of Expert (DOE) method. FTIR result revealed the intensity of peak for sulfone S=O vibration at 1322 cm-1; it was related to O=S=O bound of polysulfone in the sample. The single concentration variable has low outcome, however the mixture concentration interaction was effectively to lead better selectivity of CO2 over N2. In terms of interaction between mixture concentrations, interaction between PSF and N-Methyl-2-pyrrolidone (NMP) has considerable effect on the permeability of CO2 with the highest F value of 0.46 membrane. NMP exhibited a high degree of polarity and hydrogen bonding which led to effect of selective skin and permeation rate. The model regression equations were developed as the potential use for screening the permeability of CO2 and N2 based on the deviation effect of polymer concentration.